An in situ forming tissue adhesive based on poly(ethylene glycol)-dimethacrylate and thiolated chitosan through the Michael reaction. Issue 33 (8th August 2016) - Zeng, Zhiwen; Mo, Xiu-mei; He, Chuanglong; Morsi, Yosry; El-Hamshary, Hany; El-Newehy, Mohamed
Abstract : A novel tissue adhesive composed of CSS and PEGDMA based on the Michael addition reaction. Abstract : In this paper, a novel biocompatible and biodegradable tissue adhesive composed of poly(ethylene glycol)-methacrylate (PEGDMA) and thiolated chitosan (CSS) was prepared. PEGDMA and CSS cross-linked rapidly under physiological conditions through the Michael addition reaction via UV lamp irradiation. The chemical structures of PEGDMA and CSS were confirmed via FTIR and 1 H NMR. The equilibrium swelling ratio and biodegradation of the hydrogels were tunable by varying the component ratios of the hydrogels. The compression strength and adhesive strength of the resulting hydrogels were measured with a tensile tester, and the adhesion strength of the hydrogel was higher than the fibrin glues. Moreover, the cytotoxicity of the PEGDMA/CSS hydrogels for L929 cells was evaluated by the MTT assay, and the results indicate that the photocured hydrogels are biocompatible and less cytotoxic towards the growth of L929 cells. These findings imply that the obtained hydrogel adhesives are a potential bioadhesive for clinical application in the future.